Pearls Among Peers: A Conversation with Peer Leaders - Yanishewski, Roxanne; de Rosenroll, David (Canadian Journal of Counselling and Psychotherapy, 2011)
Six North American leaders in the field of peer counselling were interviewed about their perspectives on training and program issues, future trends, and needed research areas. The leaders' responses showed both similarities and differences and covered a broad range of concerns. These included the need for standards, cautions and concerns regarding training, differences between professional and peer counselling, the role of peer counselling in creating a caring society, and the expansion of peer counselling systems to the work force, senior citizens and Native communities.